Impact of rhizobial inoculants on rhizosphere bacterial communities of three medicinal legumes assessed by Denaturing Gradient Gel Electrophoresis (DGGE) - Pongrawee Nimnoi (2018)
Denaturing Gradient Gel Electrophoresis (DGGE) was used to study the impact of rhizobial inoculants on the rhizosphere bacterial communities of three medicinal legumes: Indigofera tinctoria, Pueraria mirifica and Derris elliptica Benth. Rhizosphere soils were collected from these legumes grown naturally in 11 provinces of Thailand. The host-specific rhizobial strains were inoculated to their hosts planted in the collected rhizosphere soils of each legume. Four months after planting, total bacterial communities DNA was extracted from the uninoculated rhizosphere soils and the inoculated rhizosphere soils. DGGE fingerprints of PCR-amplified 16S rDNA were obtained from the bacterial communities. PCR-DGGE analysis showed that the bacterial community structures in native rhizospheres of the three legumes were different from each other based on the generated dendrogram and Sorensen's index. These results suggest that different plant species and soil characteristics synergically affected the rhizosphere bacterial communities. The bacterial diversity of I. tinctoria and P. mirifica native rhizospheres were significantly different from that of D. elliptica Benth. native rhizosphere. Our results also showed that the inoculants contributed to the slight changes in rhizosphere community structures. In comparison with each other, the plants appeared to have a much stronger influence on the bacterial communities rather than the inoculants. Hierarchical cluster analysis revealed that the community structure of the inoculated rhizosphere of D. elliptica Benth. was more divergent from those of inoculated rhizospheres of I. tinctoria and P. mirifica. The ribotype richness which indicates species diversity, was highest in I. tinctoria rhizosphere, followed by P. mirifica rhizosphere and D. elliptica Benth. rhizosphere, respectively. © Springer-Verlag and the University of Milan 2010.